Comparison of interferometer calibration techniques for improved SuperDARN elevation angles - Chisham, Gareth; Burrell, Angeline G.; Marchaudon, Aurélie; Shepherd, Simon G.; Thomas, Evan G.; Ponomarenko, Pasha (Polar Science, 2021)
The high frequency radars in the Super Dual Auroral Radar Network (SuperDARN) estimate the elevation angles of returned backscatter using interferometric techniques. These elevation angles allow the ground range to the scattering point to be estimated, which is crucial for the accurate geolocation of ionospheric measurements. For elevation angles to be accurately estimated, it is important to calibrate the interferometer measurements by determining the difference in the signal time delays caused by the difference in the electrical path lengths from the main array and the interferometer array to the point at which the signals are correlated. This time delay is known as . Several methods have been proposed to estimate using historical observations; these methods are summarised in this paper. Comparisons of the estimates from the different calibration methods are presented and sources of uncertainty discussed. The effect of errors in the estimated value on the accuracy of geolocation is evaluated and discussed. The paper concludes with a series of recommendations for both scientific SuperDARN data users and SuperDARN radar operators. journal article